The Influence of Service Quality, Information Quality, and Price on Online Shopping Customer Satisfaction at the Goto Living Brand - Ichma Sevia, Frisilia; Muslim, Muslim (International Journal of Economics, Management and Accounting (IJEMA), 2024)
In today's business developments, starting with the number of retail businesses that have emerged, business competition feels increasingly tough. To face this intense competition, businesspeople must be able to compete. One way that can be done is by adding consumers and retaining them so that they become loyal customers. The purpose of this research is to determine the relationship between service quality, information quality and prices on the Goto Living online shopping site. Data collection was obtained through a questionnaire distributed online in January 2024. The author used SPSS with multiple linear regression analysis techniques. To test this research model with a sample size of 100 respondents, with a population of Goto Living customers, the sample was selected using a purposive sampling method with the criteria of male and female respondents who had shopped at Goto Living, aged 17 – 55 years, with coverage of the Jabodetabek area (Jakarta, Bogor, Depok, Tangerang, Bekasi). The results of data processing show that service quality, information quality and price have a significant influence on customer satisfaction. Future research is expected to use broader and more specific respondents with different measurement techniques. To attract new customers, as an online shop it is necessary to develop customer satisfaction by routinely controlling the service so that customers remain satisfied and loyal.